Population genetics of mouse lemur vomeronasal receptors: current versus past selection and demographic inference. Issue 1 (December 2017) - Hohenbrink, Philipp; Mundy, Nicholas; Radespiel, Ute
Abstract Background A major effort is underway to use population genetic approaches to identify loci involved in adaptation. One issue that has so far received limited attention is whether loci that show a phylogenetic signal of positive selection in the past also show evidence of ongoing positive selection at the population level. We address this issue using vomeronasal receptors (VRs), a diverse gene family in mammals involved in intraspecific communication and predator detection. In mouse lemurs, we previously demonstrated that both subfamilies of VRs (V1Rs and V2Rs) show a strong signal of directional selection in interspecific analyses. We predicted that ongoing sexual selection and/or co-evolution with predators may lead to current directional or balancing selection on VRs. Here, we re-sequence 17 VRs and perform a suite of selection and demographic analyses in sympatric populations of two species of mouse lemurs (Microcebus murinus andM. ravelobensis ) in northwestern Madagascar. Results M. ravelobensis had consistently higher genetic diversity at VRs thanM. murinus. In general, we find little evidence for positive selection, with most loci evolving under purifying selection and one locus even showing evidence of functional loss inM. ravelobensis . However, a few loci inM. ravelobensis show potential evidence of positive selection. Using mismatch distributions and expansion models, we infer a more recent colonisation of the habitat byM. murinus than byM. ravelobensis, which most likely speciated in this region earlier on. Conclusions These findings suggest that the analysis of VR variation is useful in inferring demographic and phylogeographic history of mouse lemurs. In conclusion, this study reveals a substantial heterogeneity over time in selection on VR loci, suggesting that VR evolution is episodic.